Gender: Promoting equality in fragile and conflict-affected settings - Malapit, Hazel J.; Brown, Lynn R. (International Food Policy Research Institute, 2023)
Gender inequality exists everywhere, but it is particularly stark in fragile and conflict-affected settings (FCAS). Yemen, Afghanistan, Chad, Iraq, Pakistan, and the Central African Republic — all of which are considered extremely fragile and are affected by conflict (except Pakistan) — score the lowest on the Gender Development Index. The States of Fragility 2022 report also finds that the Gender Inequality Index is highly correlated with all six dimensions used to assess fragility, with 15 of 21 conflict-affected contexts facing high levels of gender inequality. The same pattern is shown by the Global Gender Gap Report — 72 percent of the countries ranked in the bottom quartile of gender parity are considered fragile, and a numt ber of countries affected by conflict, such as Haiti, Somalia, and South Sudan, do not even have sufficient data to be included in the ranking.